A study on nutritional status among primary school children and related co-morbidities in peri urban rural setting of India - Bhoir, Prashant; Patki, Swati M.; Patki, Manoj B.; Bhoir, Jidnyasa (International Journal Of Community Medicine And Public Health, 2021)
Background: Objective of the research was to study the nutritional status of children and related co-morbidities among primary school children in peri-urban rural setting of Thane district of Maharashtra. Methods: A cross sectional study with primary data collection from government primary school in peri-urban rural setting was conducted with total study duration of one year. Children between 6 and 12 years were included in study from primary school. Schools selected using lottery system and all children present on day on examination were included. Sample size estimation by formula n=4pq/l2 which was 336, but study enrolled 402 children. Anthropometric data (BMI) was analyzed using Centers for Disease Control and Prevention (CDC) growth charts. Data was analyzed using Microsoft Excel, statistical package for the social sciences (SPSS)-17, differential and inferential statistics calculated and represented using tables and charts. Chi square test was used for statistical significance and finding association with various factors. Results: The prevalence of overweight (≥85th percentile) among children was 20.83% (male), 20.95% (female) and prevalence of obesity (>95th percentile) was 14.06 % (male), 17.62% (female). Prevalence of underweight was 4.17 % (male), 4.29% (female). Female children were at greater risk of being overweight and obese. Conclusions: Childhood obesity is a problem in peri-urban rural Thane and requires timely intervention for its control.